2000
DOI: 10.1111/j.1574-695x.2000.tb01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin (MRP8/14 protein complex) release during mycobacterial infection in vitro and in vivo

Abstract: The calprotectin (MRP8/14) protein complex belongs to the S100 family of Ca2+ binding proteins and is expressed during myelomonocytic differentiation. MRP8/14 plasma levels were determined by ELISA in 35 patients with active pulmonary tuberculosis (TB) showing mild (n = 12), moderate (n = 11) or severe (n = 12) disease, 13 patients with active pulmonary sarcoidosis (SR) and 21 healthy controls. TB patients had significantly increased plasma levels of MRP8/14 in comparison with SR and controls, which significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…6,18 Supporting this, Valheim et al 55 also found a high number of macrophages expressing Ki-67 in granulomas from subclinically paratuberculosis-affected goats, and high levels of calprotectin in plasma have been associated with severe and active tuberculosis in humans. 41 Opposed to this hypothesis, Jenkins et al 24 have pointed out that local macrophage proliferation is a signature of a Th2 inflammation. However, their study was conducted in pleural macrophages from rodents infected with a nematode, while Map is an intracellular pathogen affecting the intestine.…”
Section: Discussionmentioning
confidence: 97%
“…6,18 Supporting this, Valheim et al 55 also found a high number of macrophages expressing Ki-67 in granulomas from subclinically paratuberculosis-affected goats, and high levels of calprotectin in plasma have been associated with severe and active tuberculosis in humans. 41 Opposed to this hypothesis, Jenkins et al 24 have pointed out that local macrophage proliferation is a signature of a Th2 inflammation. However, their study was conducted in pleural macrophages from rodents infected with a nematode, while Map is an intracellular pathogen affecting the intestine.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of S100A8 and S100A9 without concomitant formation of their complex has been rarely found, eg, in a chronic type of inflammatory reaction in glomerulonephritis or in chronic renal allograft rejection 76 77. Upregulation of the S100A8/9 complex, known as calprotectin, however, has been well described in inflammatory disorders such as cystic fibrosis,78-81 psoriasis,82 tuberculosis,83 Crohn disease and ulcerative colitis 66. The presence of S100A8 and S100A9 in infiltrated macrophages in RA was first detected in 1987 84.…”
Section: Proposed Function(s) Of Other S100 Proteins In Rheumatoid Armentioning
confidence: 99%
“…In lung infections, during the course of febrile conditions (26) or tuberculosis, (27) plasma levels of calprotectin were increased, as well as in acute organ rejection, (28) and rheumatoid arthritis. (29) Furthermore, calprotectin can be measured at inflamed tissue levels, e. g., in lung MØ contained in the bronchoalveolar lavage, (30) in renal MØ and epithelial cells, (31,4) in MØ and epithelial cells from skin lesions, (32) and in the synovial membrane in the joints.…”
Section: Introductionmentioning
confidence: 99%
“…(24) Proinflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-6, released by MØ, as well as arachidonic acid mediate the expression of calprotectin (20) that in turn enhances the expression of CD11b on human MØ, thus facilitating the mechanism of extravasation. (25) The derivation of calprotectin from inflammatory cells, such as PMN and MØ, has prompted many investigations on its detection in biological fluids in different clinical settings as a biomarker of inflammation.In lung infections, during the course of febrile conditions (26) or tuberculosis, (27) plasma levels of calprotectin were increased, as well as in acute organ rejection, (28) and rheumatoid arthritis. (29) Furthermore, calprotectin can be measured at inflamed tissue levels, e. g., in lung MØ contained in the bronchoalveolar lavage, (30) in renal MØ and epithelial cells, (31,4) in MØ and epithelial cells from skin lesions, (32) and in the synovial membrane in the joints.…”
mentioning
confidence: 99%